Efficacy of interferon beta-1a plus remdesivir compared with remdesivir alone in hospitalised adults with COVID-19: a double-blind, randomised, placebo-controlled, phase 3 trial. Issue 12 (December 2021) - Kalil, Andre C; Mehta, Aneesh K; Patterson, Thomas F; Erdmann, Nathaniel; Gomez, Carlos A; Jain, Mamta K; Wolfe, Cameron R; Ruiz-Palacios, Guillermo M; Kline, Susan; Regalado Pineda, Justino; Luetkemeyer, Anne F; Harkins, Michelle S; et al.
Summary: Background: Functional impairment of interferon, a natural antiviral component of the immune system, is associated with the pathogenesis and severity of COVID-19. We aimed to compare the efficacy of interferon beta-1a in combination with remdesivir compared with remdesivir alone in hospitalised patients with COVID-19. Methods: We did a double-blind, randomised, placebo-controlled trial at 63 hospitals across five countries (Japan, Mexico, Singapore, South Korea, and the USA). Eligible patients were hospitalised adults (aged ≥18 years) with SARS-CoV-2 infection, as confirmed by a positive RT-PCR test, and who met one of the following criteria suggestive of lower respiratory tract infection: the presence of radiographic infiltrates on imaging, a peripheral oxygen saturation on room air of 94% or less, or requiring supplemental oxygen. Patients were excluded if they had either an alanine aminotransferase or an aspartate aminotransferase concentration more than five times the upper limit of normal; had impaired renal function; were allergic to the study product; were pregnant or breast feeding; were already on mechanical ventilation; or were anticipating discharge from the hospital or transfer to another hospital within 72 h of enrolment. Patients were randomly assigned (1:1) to receive intravenous remdesivir as a 200 mg loading dose on day 1 followed by a 100 mg maintenance dose administered daily for up to 9 days and up to four doses of either 44 μg interferon beta-1a (interferon beta-1a group plus remdesivir group) or placebo (placebo plus remdesivir group) administered subcutaneously every other day. Randomisation was stratified by study site and disease severity at enrolment. Patients, investigators, and site staff were masked to interferon beta-1a and placebo treatment; remdesivir treatment was given to all patients without masking. The primary outcome was time to recovery, defined as the first day that a patient attained a category 1, 2, or 3 score on the eight-category ordinal scale within 28 days, assessed in the modified intention-to-treat population, defined as all randomised patients who were classified according to actual clinical severity. Safety was assessed in the as-treated population, defined as all patients who received at least one dose of the assigned treatment. This trial is registered with ClinicalTrials.gov, NCT04492475 . Findings: Between Aug 5, 2020, and Nov 11, 2020, 969 patients were enrolled and randomly assigned to the interferon beta-1a plus remdesivir group (n=487) or to the placebo plus remdesivir group (n=482). The mean duration of symptoms before enrolment was 8·7 days (SD 4·4) in the interferon beta-1a plus remdesivir group and 8·5 days (SD 4·3) days in the placebo plus remdesivir group. Patients in both groups had a time to recovery of 5 days (95% CI not estimable) (rate ratio of interferon beta-1a plus remdesivir group vs placebo plus remdesivir 0·99 [95% CI 0·87–1·13]; p=0·88). The Kaplan-Meier estimate of mortality at 28 days was 5% (95% CI 3–7%) in the interferon beta-1a plus remdesivir group and 3% (2–6%) in the placebo plus remdesivir group (hazard ratio 1·33 [95% CI 0·69–2·55]; p=0·39). Patients who did not require high-flow oxygen at baseline were more likely to have at least one related adverse event in the interferon beta-1a plus remdesivir group (33 [7%] of 442 patients) than in the placebo plus remdesivir group (15 [3%] of 435). In patients who required high-flow oxygen at baseline, 24 (69%) of 35 had an adverse event and 21 (60%) had a serious adverse event in the interferon beta-1a plus remdesivir group compared with 13 (39%) of 33 who had an adverse event and eight (24%) who had a serious adverse event in the placebo plus remdesivir group. Interpretation: Interferon beta-1a plus remdesivir was not superior to remdesivir alone in hospitalised patients with COVID-19 pneumonia. Patients who required high-flow oxygen at baseline had worse outcomes after treatment with interferon beta-1a compared with those given placebo. Funding: The National Institute of Allergy and Infectious Diseases (USA).